Deteramination of chloramphenicol and furazolidon residues in eggs marketed in konya - Ömer DEMET; Ahmet ACET; Bünyamin TRAŞ; İsa EĞİLMEZ (Eurasian Journal of Veterinary Sciences)
In this study, chlorampenicol and furazolidon residues were determined in fifthy eggs marketed in Konya by HPLC. Furazolidon was found in seventean eggs, while no chloramphenicol in any samples. The limit level of furazolidon determined in eggs was 2.80 ug/kg, the highest level was 16.12 µg/kg. The avarage level was calculated as 7.74 µg/kg. Asa result, it was concluteq that furazolidon residues determined in eggs cause side effects for human health, while no chloramphenicol residues were evaluated as good result for consumer.